GENESA BENTONIT DI KECAMATAN WONOSEGORO KABUPATEN BOYOLALI PROPINSI JAWA TENGAH DAN REKAYASA PEMANFAATANNYA SEBAGAI BAHAN BAKU PRODUK KERAMIK (The Genetic of Bentonite at Wonosegoro Vicinity Boyolali Residency Province o - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT The research area is situated 40 kilometers north of Boyolali at Kendeng antiklinorium folding mountain. Physiographically, it lies on a thrust-fold belt, Western Kendeng Zone, Northernpart of East Java Basin. Litologic varian composing the research area consists of silisiclastic rocks, such as sandstone, siltstone, claystone, and layer of bentonite. Sedimentary character and stacking pattern showed that the sedimen was deposited by turbidit current mechanism. Wrench fault and anticline are the major structures. Shear joints and drags are occasionally found on silisiclastic sedimentary rocks layer. Antiklinorium axis is EastNortheast-WestSouthwest according to the layer position itself where is vertical. Wrench fault is Northwesat-Southeast. Bentonite was originated from material that composed of pyroclastic fall deposit which was altered. The main process was devitrivication of volcanic glasses. The other process was the solution of primary minerals and lithic fragments. The volcanic glasses consisted mostly of vitric tuff are unstable, and easy to alter in alkaline environment forming liquid which contains Si+4 cation. Meanwhile, solution of primary minerals and Ethic fragments formed liquid containing cations of